Adenosine receptors in GtoPdb v.2021.2. (2021) - Fredholm, Bertil B.; Frenguelli, Bruno G.; Hills, Rebecca; IJzerman, Adriaan P.; Jacobson, Kenneth A.; Klotz, Karl-Norbert; Linden, Joel; Müller, Christa E.; Schwabe, Ulrich; Stiles, Gary L.
No abstract available